Some Worries for J.D. Nortons Material Theory of Induction - Ducheyne, Steffen (Philosophia Naturalis, 2008)
In this essay, I take the role as friendly commentator and call attention to three potential worries for John D. Nortons material theory of induction (Norton, 2003). I attempt to show (1) that his principle argument is based on a false dichotomy, (2) that the idea that facts ultimately derive their license from matters of fact is debatable, and (3) that one of the core implications of his theory is untenable for historical and fundamental reasons.